Artikel Review: Uji Aktivitas Antibakteri Ekstrak, Fraksi dan Isolat Rimpang Curcuma sp. Terhadap Beberapa Bakteri Patogen - SILVIA PERMATA SARI; IMAM ADI WICAKSONO (Farmaka, 2016)
Curcuma sp. rhizome is a species that is often encountered in the community. The content of the common and largest of the rhizome of Curcuma sp. is the essential oils, flavonoids (curcuminoid) and terpenoids. The third component provides antibacterial activity with a force that varies depending on the levels of components in the rhizome. Tests conducted on some species of bacteria include Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, and others. Testing method of antibacterial activity is conducted disc diffusion method and the method of paper (paper disk). While the review method used was a meta-analysis. Source of data used in the form of research journal downloaded online. Journal obtained is 20 pieces and sorted to obtain 15 journals that met the inclusion criteria. Curcuma sp. used is Curcuma xanthorriza, Curcuma domestica, Curcuma longa, Curcuma mangga, Curcuma zedoria and Curcuma heyneana have antibacterial activity against several pathogenic bacteria in the form of extracts, fractions or isolates.Keywords: Curcuma sp., Antibacterial, curcuminoid, flavonoids.